Collaborative or distributed? Exploring the context-dependent variations in leadership after-school programs - Jutzi, Michelle; Aguilar, Luis; Stampfli, Barbara (Frontiers in Education, 2025)
IntroductionSwitzerland is complex and heterogenous. Since ASP have developed over the past decades without neither national guidelines nor a clear purpose, the services and programs differ considerably. Furthermore, the delineation of leadership styles, the roles and responsibilities of leaders in ASP remain ambiguous.MethodsThis empirical study describes the relationship between the organizational context of ASPs and different leadership styles. A newly developed framework of context-dependent leadership in ASP serves as a tool to interpret the commonalities between the experiences of five different ASP leaders.ResultsThe findings show that the broader municipal context shapes the way ASP leaders navigate their inter- and intra-organizational leadership role. The results indicate that ASP leaders must be flexible in their leadership styles according to the context and responsibilities.DiscussionThe results point to important nuances of collaborative and distributed leadership styles which characterize leadership in ASP and call for ASP specific leadership development strategies that account for context-dependent variations.